RETRACTED: Preface - Kwilinski Aleksy; Lyulyov Oleksii; Pimonenko Tetyana (E3S Web of Conferences, 2023)
See the retraction notice E3S Web of Conferences 456, 00002 (2023), https://doi.org/10.1051/e3sconf/202345600002